Pengaruh Temperatur Proses Austemper pada Besi Tuang Paduan Fe-Al-C Terhadap Struktur Mikro dan Sifat Mekanik - Adesty Suhandhia Putra, Muhammad Eki; Kartikasari, Ratna; Agus Jayatun, Yohanes (Retii, 2024)
The addition of aluminum (Al) to the alloy system can improve corrosion and oxidation resistance but has the disadvantage of having brittle properties, the austemper process can increase strength, toughness, reduce distortion and reduce brittle properties. The stages of the austemper process start from heating at 900oC for 1 hour, then continued immersion in molten salt (KNO3 55% + NaNO3 45%) at temperatures of 300oC, 350oC, and 400oC, for 20 minutes and continued immersion in water media. The tests carried out were microstructure tests using an optical microscope, hardness tests using the Brinnel method, and tensile strength tests. The chemical composition test results show that the Fe-Al-C alloy contains the main element Fe by 89.40%, and the main alloying element Al by 0.98%, C 5.41%, Si 1.69%, including Al alloy cast iron, Fe-Al-C alloy has a hardness of 188.2 Kg/mm2. After austemper process hardness rose to 325.4 Kg/mm2 at 300 Â° C, this is due to the change of pearlite structure into bainite structure. The tensile test results show that the Fe-Al-C alloy has a tensile stress of 188.2 Mpa and a strain value of 1.1% and then drops at austemper temperature of 300 Â° C with a tensile stress value of 44 Mpa and a strain of 0.4%, this is due to the large graphite structure and fractures and the presence of bainite structures.